Antimicrobial Resistance of Hypervirulent Klebsiella pneumoniae: Epidemiology, Hypervirulence-Associated Determinants, and Resistance Mechanisms - Lee, Chang-Ro; Lee, Jung Hun; Park, Kwang Seung; Jeon, Jeong Ho; Kim, Young Bae; Cha, Chang-Jun; Jeong, Byeong Chul; Lee, Sang Hee (Frontiers in Cellular and Infection Microbiology, 2017)
Klebsiella pneumoniae is one of the most clinically relevant species in immunocompromised individuals responsible for community-acquired and nosocomial infections, including pneumonias, urinary tract infections, bacteremias, and liver abscesses. Since the mid-1980s, hypervirulent K. pneumoniae, generally associated with the hypermucoviscosity phenotype, has emerged as a clinically significant pathogen responsible for serious disseminated infections, such as pyogenic liver abscesses, osteomyelitis, and endophthalmitis, in a generally younger and healthier population. Hypervirulent K. pneumoniae infections were primarily found in East Asia and now are increasingly being reported worldwide. Although most hypervirulent K. pneumoniae isolates are antibiotic-susceptible, some isolates with combined virulence and resistance, such as the carbapenem-resistant hypervirulent K. pneumoniae isolates, are increasingly being detected. The combination of multidrug resistance and enhanced virulence has the potential to cause the next clinical crisis. To better understand the basic biology of hypervirulent K. pneumoniae, this review will provide a summarization and discussion focused on epidemiology, hypervirulence-associated factors, and antibiotic resistance mechanisms of such hypervirulent strains. Epidemiological analysis of recent clinical isolates in China warns the global dissemination of hypervirulent K. pneumoniae strains with extensive antibiotic resistance in the near future. Therefore, an immediate response to recognize the global dissemination of this hypervirulent strain with resistance determinants is an urgent priority.